EVALUATION OF OPERATION SYNERGY, OPTIMAL FINANCING MIX AND DIVIDEND DECISION TO MAXIMIZE THE VALUE OF BUSINESS IN INALUM HOLDING OF MINING - Tri Widodo, Ridho
Many strategic investments are often justified with the argument that they will create synergy. According Inalum, the goal on holding mining establishment were more on how to increase business capacity and funding, management of natural resources of mineral and coal, increase value added through downstream and increase local content, as well as cost efficiency through synergy. This paper aims to evaluate the value of operating synergy in Inalum , PTBA, ANTM and TINS before establishment holding company of mining and the sensitivity the value to different assumptions, to find the optimal mix of debt and equity to maximize firm value, to find the right kind of debt, and the implementation plan. In this valuation of operation synergy, Discounted Cash Flow (DCF) Framework will be used to recognize the potential source of synergy from operation. In finding the optimal financing mix, the cost of capital approach will be used. This study found that gain from operation synergy of increasing growth and cost reduction will maximize the business value amounted USD 3,659,295.63, compared to gain from cost reduction USD -14,181,427.91 and gain from increasing growth USD 644,448.44. Based on calculation for capital structure, there is maximum value of the firm at particular debt ratio. PTBA has optimal debt ratio at 30 percent, while PTBA current debt ratio was 14.32 percent. ANTM has optimal debt ratio at 10 percent, while PTBA current debt ratio was 4.04 percent. TINS has had optimal debt ratio in 19.87 percent, this resulted optimal firm value. For matching tenor of asset cash flow to cash flow liabilities has been done, Macaulay duration is used. PTBA has modified Duration was 8.8 years, ANTM has 6.2 years. PTBA has opportunity to add the debt up to Rp 5,271,548 million on top of its current debt. ANTM has an option returning cash up to Rp 1,335,807.90 million to owner by buyback stock. Given the results from study, it is important to derive the right strategy from investment decision to reflect the optimal source of synergy in order to maximize the business value in Inalum. PTBA and ANTM still had potential to improve their optimal financing mix, while TINS was on its optimal financing mix. For funding the operation, this thesis will propose to issue bond.